The Relationship Between Social Learning and Juvenile Delinquency in High School Students - Annisa Fadillah (Universitas Pendidikan Ganesha, 2024)
Juvenile delinquency is a phenomenon that continues to grow alongside social changes and progress, affecting the psychological development of adolescents, who are often emotionally unstable. This study aims to analyze the causes of juvenile delinquency among students at Melati Binjai Private High School and to identify the contributing factors, as well as the strategies used to address this issue. The approach used in this study is quantitative, employing a correlational method. The subjects of the study consisted of 30 private high school students selected through purposive sampling. Data were collected using two instruments: a juvenile delinquency scale and a social learning scale, both measured using a Likert scale. Data were analyzed using the Pearson Product-Moment correlation. The results of the study showed no significant relationship between social learning methods and juvenile delinquency. This finding suggests that other factors—such as parenting styles, social environment, and peer interactions—may have a greater influence on delinquent behavior. The study concludes that social learning alone is insufficient to address juvenile delinquency and recommends that additional factors be considered in efforts to prevent such behavior. The implications of this research are important for various stakeholders, particularly educators, schools, and policymakers in the field of education.